STUDI KRITIS TERHADAP KRITIK NALAR ARAB MUHAMMAD ABED AL-JABIRI - Mustofa, Imam (ISTINBATH JURNAL HUKUM, 2010)
AbstractThis article traits to discuss Mohammad Abed al-Jabiris critical Arab reason project. As result of study, the author found that Al-Jabiri projected his self in the specific ideas project. He tried to build and bring Islam to improvement based on reality. He poured building of epistemology to three concepts "trilogy of concepts"Â  which spread in his three books. First, TakwÄ«n al- âAql al âArabÄ« (Formation of Arab Reason, 1982), second, Bunyah al-âAql al-âArabÄ« (Strutructure of Arab Reason, 1986), and third, al âAql as-SiyÄsÄ« al-âArabÄ« (Political Arab Reason, 1990). Al-Jabiri concerned on themes which often appear in Arabic language environment. Al-Jabiri return Arab reason structure to three compositions; first, Original Arab composition which he called religious rationality or reason of explication which illustrated in the linguistics and religious science. Second, Greece composition or Aristotelian which he called rationality of rational or demonstrative-cosmologic reason which illustrated in the philosophy and its sciences. Third, old compositionÂ  he called irationality of rational future reason and it was illustratredÂ  in the gnostic. In the critical arab reason project, Al-Jabiri discussed many things, but he also leaved many things. He alienatedrationality area at dicipline of knowledge which illustrated in the sufism (gnostic) traditions.Â Keywords: Critique, demonstrative-cosmologic-gnostic.